Optimization of complex therapy and rehabilitation of the musculoskeletal system in osteosarcopenia and vitamin D deficiency in postmenopausal women - Turchin, N. I. (Journal of Education, Health and Sport, 2020)
Osteosarcopenia, i.e. combination of low muscle mass and reduced bone mineral density, is associated with aging and recognised as public health burden. The objective: to determine the possibility of treatment and rehabilitation to increase the functional capabilities of the musculoskeletal system in OSP and vitamin D deficiency in postmenopausal women. Materials and methods. 178 women aged 55.7 ± 0.6 years old, among them 148 OSP patients. Densitometry was performed, 25 (OH) D level in blood serum, C - terminal telopeptide, degradation product of type 1 collagen (CTx) were determined, functional tests were used. Results and conclusions. Complex use of physical rehabilitation (multifunctional trainer "HUBER") in combination with drug therapy (vitamin D, denosumab) promotes more effective increase of the functional capabilities of the musculoskeletal system: muscle strength, stability, coordination of movements, reduces functional limitations; promotes more effective treatment of structural and functional changes in bone tissue, increase BMD. Functional tests of the state of musculoskeletal tissue falls and are highly informative in terms of predicting the risk of fractures (impaired coordination and FraxAll, stability and FraxAl, risk of falls and FraxAll, dynamometry and FraxAll.